Eugenics and Freemasonry in the Banat during the first half of the XX Century: The Banat-Crişana Social Institute - Varga, Attila (DELTOS, 2024)
The present study highlights the beginning of the dissemination of eugenic ideas in Banat, Caraș and the Severin counties, in two different phases: before and after the World War I. On the basis of archival documents, we have shown that Freemasonry, namely the “Dél” (South) Lodge of Lugoj, played an important role in the dissemination of eugenic ideas in the aforementioned area. After the Great Union of 1918, eugenics activism in the province was taken over by the members of the prestigious Banat-Crișana Social Institute, founded in 1932. Nevertheless, the role of Freemasonry in spreading eugenic ideas did not diminish in this new period. This is due to cultural and scientific personalities such as Cornel Grofșorean, who was a publicist, journalist, politician, director of the Institute’s journal, but also a Freemason in the Lugoj Lodge.